CONTENT ANALYSIS OF BAHASA INGGRIS TEXTBOOK USED BY THE ELEVENTH GRADE STUDENTS OF SENIOR HIGH SCHOOL - Nabila (UNMUH BABEL PRESS, 2020)
The purpose of this research was to find out the feasibility of all chapters in Bahasa Inggris textbook for the eleventh-grade students of senior high school. The feasibility in this term refers to the content feasibility from BSNP (Badan Standar Nasional Pendidikan). This study used qualitative research and content analysis as the method of this research. The data collected of this research were collected from the core and basic competence of English subject for eleventh grade students of senior high school, rubric assessment, and Bahasa Inggris textbook for eleventh grade students of senior high school which published by the Ministry of Education and Culture of Indonesia. The result of this research shows that the score of content feasibility is 3.1, which means the content feasibility of Bahasa Inggris textbook for eleventh grade students of senior high school is ‘good’. Based on the result of this study, all chapters of the textbook have fulfilled all sub-components of the content feasibility from BSNP.